2021
DOI: 10.2174/1386207323999201027225305
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Thymoquinone as Anticancer Agent

Abstract: Abstract:: Thymoquinone (TQ), the bioactive constituent of Nigella Sativa seeds is a well-known natural compound for the management of several types of cancers. The anti-cancer properties of thymoquinone are thought to be operated via intervening with various oncogenic pathways including cell cycle arrest, prevention of inflammation and oxidative stress, induction of invasion, metastasis, inhibition of angiogenesis, and apoptosis. As well as up-regulation and down-regulation of specific tumor suppressor genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…TQ is known as an anti-tumour candidate compound that is characterized by its small molecular size, and recent studies have touched on its biological function and mechanism of action. 20,[30][31][32] While the mechanism and targets of TQ have become the focus of current research, the compound itself fails to exhibited strong anti-tumour effects in numerous cancer -cell studies, which limited the potential of TQ in clinical drug development. 33 Katharina EN et al 34 showed the compounds with unsaturated side chains conferred a greater activity than those compounds with equally long saturated chains, but the in vivo efficacy was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…TQ is known as an anti-tumour candidate compound that is characterized by its small molecular size, and recent studies have touched on its biological function and mechanism of action. 20,[30][31][32] While the mechanism and targets of TQ have become the focus of current research, the compound itself fails to exhibited strong anti-tumour effects in numerous cancer -cell studies, which limited the potential of TQ in clinical drug development. 33 Katharina EN et al 34 showed the compounds with unsaturated side chains conferred a greater activity than those compounds with equally long saturated chains, but the in vivo efficacy was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone (THQ) is extracted from the medicinal plant Nigella sativa (Ranunculaceae Family), famous by black seed, nutmeg flower or fennel flower [36]. It possesses pharmacological activity against oxidative stress, inflammation, and against cancer as well [37]. THQ (i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 15 - 19 The anticancer properties of TQ induced their anticancer potential through prevention of inflammation and oxidative stress, inhibition of angiogenesis and metastasis, induction of apoptosis, upregulation of specific tumor suppressor genes, and downregulation of tumor-promoting genes. 20 The anticancer effect of TQ is mainly due to the induction of apoptosis by activation of caspases, downregulation of oncogenes, inhibition of NF-κB, reactive oxygen species regulation, hypoxia, and anti-metastasis activity. 21 Furthermore, TQ inhibited various tumor cells’ proliferation via induction of cell cycle arrest, disruption of the microtubule organization, and downregulation of cell survival protein expression.…”
Section: Introductionmentioning
confidence: 99%